EFEKTIFITAS PENERAPAN PENGENDALIAN INTERN (INTERNAL CONTROL) TERHADAP PENGUKURAN KINERJA DINAS PENDAPATAN DAERAH KABUPATEN MINAHASA TENGGARA PROVINSI SULAWESI UTARA - Patik, Pancisto; Tinangon, Jantje; Tirayoh, Victorina Z. (JURNAL RISET AKUNTANSI GOING CONCERN, 2016)
The system of internal control is a process that is integral to the actions and activities carried out on an ongoing basis by management and all employees to provide reasonable assurance on the achievement of organizational goals through effective and efficient, the reliability of financial statements, safeguarding state assets, and compliance with laws -invitation. The purpose of this study was to determine the effectiveness of the implementation of internal control of the performance of the Department of Revenue Southeast Minahasa Regency. This research method is descriptive research. Based on the results of research and discussion can be seen that the Internal Control System (Internal Control) on the performance of the Department of Revenue Southeast Minahasa Regency North Sulawesi province has been run "effective" because it was done separation of duties and responsibilities are clear, the forms that were used in the reception area already contains information that is reliable, and the achievement of revenue targets revenue in 2015 has been effective, while the main tasks in the organization are based on Government Regulation No. 60 of 2008 concerning the Government Internal Control System (SPIP) is adequate. Keyword: PAD Admission Control Procedures and Control Organization Department of Revenue Southeast Minahasa Regency.